ECG ABNORMALITIES IN RURAL AREAS - M. Daneshapjooh; A. Nadim; H. Amini (Tehran University of Medical Sciences, 1975)
A survey was carried out in the summer of 1972 in east Azerbaijan, northwest Iran, to determine the prevalence of cardiovascular disease. ECG tracings were prepared from 198 women and 178 men aged 40-60. Only 45% of the tracings were completely normal. Q/QS abnormalities were found in 4.7% of tracings, left axis deviation in 4% tall R wave in 37%, ST depression in 3.9% of men and 14.1% of women and T wave inversion in 2.2% of men and 11.6% of women. Further studies are recommended to explain this high prevalence of ST depression and T wave inversion in the women of this area.